Das literarische Gesicht im Werk Heinrich von Kleists und Franz Kafkas - Vitale, Claudia (Biblioteca di Studi di Filologia Moderna, 2011)
The topics of physicality and face in Kleist and Kafka as well as the problem of perception, which are the focus of this work, fit seamlessly into the context of a fruitful exchange of different scientific experiences. The present work underlines and promotes a double perspective: the methodology of German studies, which is based on philosophy and cultural anthropology, on the one hand, and the literary and art-historical approach of the Italian, historical and humanistic tradition on the other, which is still clinging, in a certain way, to the canon of beauty of the late Renaissance.